Kewenangan Pengadilan Negeri Jakarta Pusat Dalam Kaitannya Dengan Pembatalan Putusan Arbitrase Internasional Ditinjau Dari Kasus Antara Karaha Bodas Company, Pertamina dan PLN - ., Hendra; Widjaja, Gunawan; Rusli, Hardijan (Pelita Harapan University, 2004)
Freedom of contract gives flexibility to litigants in determining choice of law, choice of jurisdiction, and choice of domicile. In the unlimited business era nowadays, arbitration is a very popular forum for businessmen in many countries in settling civil disputes outside the courts, because of the simple procedure and relatively fast result compared to the court procedure. Besider the arbitration award is not for public exposure, which is very important for the businessmen who their credibility. On the other hand, businessmen who have won the case are when it comes to the enforcement of the arbitration award which have to involve the court. The most common thing that happened is that mostly the losing party will ask for a annulment or refusal of the arbitration award in the country where the award will beexecuted. In Indonesia, according to the article 70, 71, and 72 Undang-Undang No. 30/1999 concerning arbitration and alternative dispute resolutions, the authority to annul an arbitration award is in the hand of the district court. In article 70 Undang-Undang No. 30/1999 it is mentioned that the parties can file an application to annul an arbitration award if any of the following conditions are alleged to exist : 1. Letters or documents submitted at the hearings are acknowledged to be false or forged or are declared to be forgeries after the award has been rendered; 2. After the award has been rendered there are documents found which are decisive in nature and which deliberately concealed by the opposing party; or 3. The award was rendered as result of fraud committed by one of the parties to the dispute. In the Case between Karaha Bodas Company, PERTAMINA, and PLN, the District Court of Central Jakarta has an authority to annul the Geneva arbitration award according to is only valid the conditions in article 70 Undang-Undang No. 30/J999, but the annulment award can only be used in Â the Indonesian law territory, it is not an obligation for other courts in other countries to the follow the annulment award, due to State Sovereignty of every country. An annulment of Geneva arbitration award, in order to admitted and enforced by each country, must be done by the court in Geneva, Swiss in which the arbitration award has been given, or according to the law by which the award has been given. This is according to article V (])e New York Convention 1958.Â